Analisis Kompetensi Pedagogik Guru Geografi dalam Pembelajaran Geografi di SMA Negeri Kabupaten Pemalang Tahun 2019 - Yanuar, Rizki; Sriyanto, Sriyanto (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2021)
The objectives of this study were to 1) determine the pedagogical competence of geography teachers of public high schools in Pemalang Regency, 2) the driving and inhibiting factors for teacher pedagogical competence in geography learning in public high schools in Pemalang Regency. The population in this study were geography teachers and high school students in Pemalang Regency. Determination of the research sample using total sampling technique for geography teachers and proportionate srtatified random sampling for students. The variables of this research are teacher pedagogical competence with sub-variable level of teacher geography pedagogical competence, as well as driving and inhibiting factors of teacher pedagogical competence in geography learning. Data collection techniques using questionnaires, observation, interviews, and documentation. Data analysis using descriptive statistical analysis techniques. Based on the research, it shows that: 1) the pedagogical competence of the georaphic teachers of SMA Negeri in Pemalang Regency is included in good criteria, supported by student responses that are included in good criteria, and the results of the observation of teacher pedagogic competence in geography learning are also included in good criteria. 2) The driving and inhibiting factors for teacher pedagogical competence in geography learning are the availability of facilities and infrastructure, competency development programs, utilization of ICT-based learning media, and supervision of school principals. Tujuan dalam penelitian ini adalah untuk 1) mengetahui kompetensi pedagogik guru geografi SMA Negeri di Kabupaten Pemalang, 2) faktor pendorong dan penghambat kompetensi pedagogik guru dalam pembelajaran geografi SMA Negeri di Kabupaten Pemalang. Populasi dalam penelitian ini adalah guru geografi dan siswa SMA Negeri di Kabupaten Pemalang. Penentuan sampel penelitian menggunakan teknik total sampling untuk guru geografi dan proportionate srtatified random sampling untuk siswa. Variabel penelitian ini adalah kompetensi pedagogik guru dengan sub variabel tingkat kompetensi pedagogik guru geografi, serta faktor pendorong dan penghambat kompetensi pedagogik guru dalam pembeljaran geografi. Teknik pengumpulan data dengan kuesioner, observasi, wawancara, dan dokumentasi. Analisis data menggunakan teknik analisis statistik deskriptif. Berdasarkan penelitian, menunjukan bahwa: 1) kompetensi pedagogik guru georafi SMA Negeri di Kabupaten Pemalang termasuk dalam kriteria baik, didukung respon siswa termasuk dalam kriteria baik, dan hasil observasi kompetensi pedagogik guru dalam pembelajaran geografi juga termasuk dalam kriteria baik. 2) faktor pendorong dan penghambat kompetensi pedagogik guru dalam pembelajaran geografi adalah ketersediaan sarana dan prasarana, program pengembangan kompetensi, pemanfaatan media pembelajaran berbasis TIK, serta pengawasan kepala sekolah.